Factors affecting consumer purchase and usage behaviour of social commerce: a case of perishable pastry products / Faradewi Bee A. Rahman - A. Rahman, Faradewi Bee (2021)
Social media development has generated a new model of electronic commerce, called social commerce. The social commerce model combines commercial and social media activities by integrating social technologies into e-commerce. Previously through e-commerce, small and medium entrepreneurs products such as groceries and pastries have lower acceptance value among online consumers as they are easily perishable. Since then, social commerce has allowed small and medium entrepreneurs, especially those selling perishable products, to target and engage the broader online consumer markets. However, little empirical research exists on consumers' social commerce acceptance and usage, especially on perishable foods such as pastry products. Thus, this study investigates the inter-relationship between social commerce acceptance and usage determinants, trust, purchase behaviour, and pastry products consumers. In addition, this study also assesses whether age generation moderates the relationship between social commerce acceptance and usage determinants and pastry products consumers' purchase behaviour. Data was collected from 409 pastry consumers through an online survey. Data were analysed using SPSS version 24 and SmartPLS version 3.1.1 software. The study findings primarily indicate that pastry consumers perceived social commerce as engaging, enjoyable, and simple to use and saves time. In addition, the results show that peer control has the most significant impact on social commerce usage among the younger generations. The study findings contribute to the technology acceptance theory by understanding the determinants of technology adoption among social commerce consumers. Such perspectives contribute to the body of knowledge, theoretical, and methodological aspects.